1965
DOI: 10.1002/ijch.196500044
|View full text |Cite
|
Sign up to set email alerts
|

The Course of N‐Alkylation of 6‐Methylmercaptopurines

Abstract: Reaction of a 6-methylmercaptopurine with methyl iodide in an aprotic solvent gives only a single methylation product. Both the 7-and the 9-methyl derivatives are alkylated at N-3. 3-Methyl-6-methylmercaptopurine is attacked at N-7, while the I-methyl isomer is substituted at position 9. The course of the latter reaction depends markedly on the reaction conditions, as in the presence of an alkali carbonate alkylation takes place at N-7. The mechanism of these methylations is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
2
1

Year Published

1967
1967
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
9
2
1
Order By: Relevance
“…Recently, Montgomery et al [3] reported that I-benzyl-6-thiopurine (V), when heated with benzyl chloride in dimethylacetamide, yields a mixture of the 1,7-(VII) and 1,9-dibenzyl derivatives (VIII) (see Scheme B). At first glance, this observation is in disagreement with our earlier finding that the substitution of 1-melhyl-6-methylmercaptopurine depends on the form of substrate used: The free base underwent alkylation exclusively at N-7 and the salts at N-9 [1]. Since Montgomery et al started with the 6-thio compound, the first product in their reaction was the hydrochloride of 1-benzyl-6-benzylmercaptopurine (VI), which at the temperature used (140 0 ) may suffer partial dissociation to the free base.…”
Section: Br -contrasting
confidence: 99%
See 2 more Smart Citations
“…Recently, Montgomery et al [3] reported that I-benzyl-6-thiopurine (V), when heated with benzyl chloride in dimethylacetamide, yields a mixture of the 1,7-(VII) and 1,9-dibenzyl derivatives (VIII) (see Scheme B). At first glance, this observation is in disagreement with our earlier finding that the substitution of 1-melhyl-6-methylmercaptopurine depends on the form of substrate used: The free base underwent alkylation exclusively at N-7 and the salts at N-9 [1]. Since Montgomery et al started with the 6-thio compound, the first product in their reaction was the hydrochloride of 1-benzyl-6-benzylmercaptopurine (VI), which at the temperature used (140 0 ) may suffer partial dissociation to the free base.…”
Section: Br -contrasting
confidence: 99%
“…In a suitable aprotic solvent (DMF or acetonitril), 6-methylmercaptopurine (I) undergoes benzylation first in position 3 (II) and subsequently at N-7 (III). However, in this reaction chain the conversion of (II) to (III) is not restricted to the free base of the former, in contrast to our previous report on the reaction of (I) with methyl iodide [1], and to the observation of Montgomery and Thomas [2] that 3-benzyladenine can undergo 7-alkylation only, when present as the free base. Therefore, dibenzylation of (I) to (III) can be accomplished in a single run, the composition of the end-products depending on the benzyl halide used (see Table III).…”
Section: Introductioncontrasting
confidence: 63%
See 1 more Smart Citation
“…As part of our present research work we are preparing acylated derivatives of tertbutyl 6-(9H-purin-6-ylthio) hexylcarbamate. According the Neiman and Bergmann [10] work we confirmed that acylation at the 9-position.…”
Section: Introductionsupporting
confidence: 53%
“…Thus treatment of the free base of IV with methyl iodide in DMF gave the 3,7-dimethyl derivative (VI), in analogy to the behavior of II [6]. The structure of VI follows from its thiohydrolysis to the known 3,7-dimethyl-6-thiopurine (VIII).…”
mentioning
confidence: 87%